2014
DOI: 10.1007/s13277-014-1814-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of RCAS1 as a biomarker in diagnosing CRC and monitoring tumor recurrence and metastasis

Abstract: Receptor-binding cancer antigen expressed on SiSo cells (RCAS1) plays an important role in tumor progression by helping tumor cell to escape from host immunological surveillance or modifying the characteristics of connective tissue around. RCAS1 may appropriately reflect the development and prognosis of tumor. In the study, we sought to identify the clinical significance of RCAS1 in colorectal cancer (CRC) diagnosis and tumor recurrence monitoring. Immunohistochemistry (IHC) with tissue array slides was prefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…3,4 As suggested by existing studies, some factors exert vital parts in CRC relapse and metastasis, such as tumor location, clinicalpathologic stratification, K-ras mutations, microsatellite instability, mismatch repair genes, COX-2 expression, circulating tumor DNA, gut microbiota, and so on. [5][6][7][8][9][10] However, these factors do not exhibit adequate reliability for predicting recurrence. Therefore, there remains an urgent to appraise valuable clinical entities and biomarkers aiming to identify patients at risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 As suggested by existing studies, some factors exert vital parts in CRC relapse and metastasis, such as tumor location, clinicalpathologic stratification, K-ras mutations, microsatellite instability, mismatch repair genes, COX-2 expression, circulating tumor DNA, gut microbiota, and so on. [5][6][7][8][9][10] However, these factors do not exhibit adequate reliability for predicting recurrence. Therefore, there remains an urgent to appraise valuable clinical entities and biomarkers aiming to identify patients at risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that tumor RCAS1 expression is an indicator of poor prognoses in patients with cancer [16,[24][25][26][27][28][29]. However, there is sparse data on serum sRCAS1 levels as a prognostic factor in human malignancies, and most of the data that does exist relates to the evaluation of short term outcomes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Similar data were obtained in the study on colorectal cancer. The authors revealed that serum sRCAS1 levels decreased significantly in patients treated for colorectal cancer and increased at the time of recurrence . Sonoda et al .…”
Section: Discussionmentioning
confidence: 99%
“…The authors revealed that serum sRCAS1 levels decreased significantly in patients treated for colorectal cancer and increased at the time of recurrence. 29 Sonoda et al reported a significant decrease in the serum sRCAS1 levels of patients following the successful treatment of cervical and endometrial carcinomas. Furthermore, an increase in the protein levels was observed with tumor progression.…”
Section: Discussionmentioning
confidence: 99%